Harmonisasi Hukum dan Kebijakan dalam Penegakan Hukum Lingkungan - Rikawati, Ferdiana; Lestari, Dwi Indah (Indonesian Journal of Law and Justice, 2024)
Law is also a policy product, but policy may not be a legal product. This often becomes a problem later, because policies move more flexibly than existing legislation, although policies must still not be separated from the basic meaning of existing and currently applicable laws. Thus, as a necessity, the law cannot be too restrictive for policy to move, so that policy loses its elasticity which at certain times is needed in the application of the law itself. As understood, law enforcement is not merely implementing existing texts without paying attention to the conditions in the environment and the most important thing is highlighting the essence of justice, which ultimately manifests as wisdom.